2019
DOI: 10.1002/ejsp.2629
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive measure of attitudes and behaviour: Development of the Support for Gender Equality among Men Scale

Abstract: In this article, we develop and validate the 16‐item Support for Gender Equality among Men Scale across four studies. Drawing on exploratory (Study 1, n = 322) and confirmatory (Study 2, n = 358; Study 4, n = 192) factor analysis, we determine a two‐factor structure: public and domestic support for gender equality. In Study 3 (n = 146) and Study 4, we validate the scale by establishing its relationship with, among others, several prominent measures of sexism, a behavioural measure, and social desirability. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 138 publications
(193 reference statements)
0
15
0
Order By: Relevance
“…The illusory antagonism between BS and each of these variables was strengthened by the perception that these attitudinal and behavioral displays corresponded with men who were low (vs. high) warmth toward women. In the same vein, previous research has indicated that men higher on BS are no more likely than men lower on BS to take action to support gender equality (such as sharing domestic duties equally or participating in collective action; Drury & Kaiser, 2014;Sudkämper et al, 2018), and are less likely to support abortion rights (Huang et al, 2016), Nonetheless, in this study, perceptions of BS were positively associated with these characteristics, because they were seen to be displayed by men with warm attitudes toward women.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The illusory antagonism between BS and each of these variables was strengthened by the perception that these attitudinal and behavioral displays corresponded with men who were low (vs. high) warmth toward women. In the same vein, previous research has indicated that men higher on BS are no more likely than men lower on BS to take action to support gender equality (such as sharing domestic duties equally or participating in collective action; Drury & Kaiser, 2014;Sudkämper et al, 2018), and are less likely to support abortion rights (Huang et al, 2016), Nonetheless, in this study, perceptions of BS were positively associated with these characteristics, because they were seen to be displayed by men with warm attitudes toward women.…”
Section: Discussionmentioning
confidence: 97%
“…Participants responded on a scale from 1 ( not at all ) to 8 ( very much ) to the following group-level items: “willing to protest, sign petitions and take other action to support equality for women” ( Public Support Equality ; Becker & Wright, 2011), “willing to split housework equally with their wives/partners” ( Domestic Support Equality ; Sudkämper et al, 2018), “Supports a woman’s legal right to have an abortion on grounds other than to protect her physical health (e.g., poverty, does not want a child, has no partner)” ( Support Elective Abortion ; Huang et al, 2016), “Supports a woman’s legal right to have an abortion when it is essential for her physical health” ( Support Traumatic Abortion ; Huang et al, 2016), “disapproves of breastfeeding in public” ( Disapprove Public Breastfeeding ; Acker, 2009), “believes that the relationship between men and women is fair and equal” ( Gender Status Quo ; Jost & Kay, 2005), “would blame a woman for being raped by a man with whom she is having an extramarital affair” ( Blame Rape Victim ; Viki & Abrams, 2002), “Minimizes and justifies domestic violence perpetrated by men against their wives/partners” ( Justify Domestic Violence ; Glick et al, 2002), “would try to prevent pregnant women from doing what they want, if (s)he thinks their choices could harm the fetus/baby” ( Pregnant Women’s Choices ; Sutton et al, 2011), and “Laughs at sexist jokes and doesn’t find them offensive” ( Enjoy Sexist Humor ; Eyssel & Bohner, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the social importance of achieving a more equal distribution of domestic tasks, and the increasing scientific interest in this phenomenon (e.g., Sudkämper, Ryan, Kirby, & Morgenroth, 2019; for a review, see Meeussen, Van Laar, & Van Grootel, 2020), the goal of the present research was to identify a potential barrier to men's greater inclusion in the domestic sphere; namely, cross-gender helping in conducting domestic tasks. The literature on intergroup helping relations suggests that help behavior is often a subtle, nonconflictual means to reinforce existing (unequal) social arrangements (Nadler, 2002).…”
Section: -Letty Cottin Pogrebinmentioning
confidence: 99%
“…However, many men support gender equality, and some identify as feminists, work to combat sexism, and serve as feminist advocates and educators (Bojin, 2013; Drury & Kaiser, 2014; Edwards, 2008). Recent research has begun to examine the role of men in the feminist movement (Iyer & Ryan, 2009; Madsen et al, 2020; Stewart, 2016; Sudkämper et al, 2020; Wiley & Dunne, 2019), but men’s feminist identity development process remains elusive. The present study aimed to address this gap in the literature by exploring men’s lived experiences of feminist identity growth and identifying potential barriers to men’s feminist advocacy and activism.…”
Section: Feminist Stigma and Stereotypesmentioning
confidence: 99%